Didactics and its relationship with the design of learning environments: a view from the teaching of the evolution of technology (2014)
The area of technology and computers is one of the nine areas established as mandatory in the Colombian basic education level. Because of its importance, the design of a learning environment oriented to the teaching of the evolution of technology during the Industrial Revolution is described in this paper. Taking into account a diagnostic test, the learning needs of the students were established and a learning environment is developed based on a model called “pedagogical content knowledge”. For the design of the learning environment, it was considered “a strategy for the task”, where the goals were to identify the stages of the evolution of technology during the industrial revolution, to argue about the facts which generate technological changes during that period, and at the same time, to know about the ancestors of some technological devices which exist at the moment. The instructional design was implemented with 24 seventh graders from the school “Liceo La Presentación”, in Sogamoso, Boyacá. As a result of the classroom activity, students made time lines about the evolution of transportation vehicles, communication processes and some technological artefacts. The implementation of the proposed environment allowed to establish the importance of generating training spaces, where students ask themselves and be able of demonstrate the knowledge appropriation, in order to establish the relationship with their social environment.